PRIMERAS IMPRESIONES SOBRE EL PROFESOR: REFLEXIONES DE LOS PRIMEROS AÑOS DE EJERCICIO. - Sergio Rykio Kussuda (Universidad Distrital Francisco José de Caldas, 2011)
This paper present some reflections about factors that could be better discussed on graduation classes, reflections did during two years working as teacher and, at same time, doing a master course main to teach science. In this paper are presented discussions about the way of assignment of classes and the consequences of that kind of assignment, the knowledge acquired with interaction of more experienced teachers, the consequences due to leak of time and the apparent powerlessness of teacher on a classroom.